Traces of Māturīdīsm in the ‘Ulamā’s Works in Nusantara in the Seventeenth Until Nineteenth Centuries - Bindaniji, Muhamad (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2020)
This study challenges the prevailing assumption that theological discourse in the Malay–Indonesian world (Nusantara) has been exclusively shaped by Ashʿarism. It seeks to demonstrate that Māturīdism developed alongside Ashʿarism through transregional scholarly networks and constituted an integral component of Sunni theological formation in Nusantara. The research employs a qualitative historical approach grounded in manuscript and library-based study. It examines theological works produced by Nusantara ʿulamāʾ between the seventeenth and nineteenth centuries, situating them within broader global networks of Islamic intellectual exchange. Particular attention is given to patterns of transmission, doctrinal articulation, and terminological usage that indicate the presence of Māturīdī theological reasoning. The study finds that theological discourse in Nusantara represents a continuous extension of global Sunni kalām traditions rather than a singular Ashʿarī trajectory. While Ashʿarism became more institutionally visible, Māturīdī theological elements were also transmitted, adapted, and embedded within local scholarly production. The two traditions functioned not as competing doctrines but as complementary strands within Sunni orthodoxy. Māturīdism in Nusantara is thus identifiable as a method of theological reasoning characterized by moderation, rational balance, and doctrinal equilibrium. By foregrounding the presence of Māturīdism, this study reconfigures the intellectual map of Islamic theology in Nusantara and underscores its integration within wider Sunni networks. It contributes to Southeast Asian Islamic historiography by demonstrating the plurality of theological genealogies and by offering a renewed perspective on the methodological foundations of Sunni thought in the region.